2023
DOI: 10.5935/0004-2749.20230068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tricyclic antidepressants, selective serotonin reuptake inhibitors, and selective serotonin-norepinephrine reuptake inhibitors on the ocular surface

Abstract: This study aimed to investigate the effects of tricyclic antidepressants, selective serotonin reuptake inhibitors, and selective serotonin noradrenaline reuptake inhibitors on the ocular surface. Methods: The study included 330 eyes of 165 patients using antidepressants and 202 eyes of 101 controls. Tear fluid breakup time, Schirmer I test, and Ocular Surface Disease Index (OSDI) questionnaire were administered. Beck Depression Inventory and Beck Anxiety Inventory were applied to record drug use, dosages, psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…As was shown in a recent study, patients using SNRIs have lower OSDI scores than patients using SSRIs or TCAs. It suggests that among the most common antidepressants, SNRIs seem to have the least exacerbating impact on dry eye symptoms, which can be caused by their pain-reducing properties as they are also used in the treatment of chronic pain syndromes [57]. Other psychotropics were also shown to be associated with DED.…”
Section: Comorbidities and Medicationsmentioning
confidence: 99%
“…As was shown in a recent study, patients using SNRIs have lower OSDI scores than patients using SSRIs or TCAs. It suggests that among the most common antidepressants, SNRIs seem to have the least exacerbating impact on dry eye symptoms, which can be caused by their pain-reducing properties as they are also used in the treatment of chronic pain syndromes [57]. Other psychotropics were also shown to be associated with DED.…”
Section: Comorbidities and Medicationsmentioning
confidence: 99%
“…In the sub-groups, reported that patients taking SSRI had worse findings than patients taking SNRI. 9 In another study, all dry eye tests and tear meniscus parameters were found to be significantly lower in the antidepressants group (Schirmer test, 11,4 ± 6,7 mm vs 22,5 ± 5 mm; TBUT, 5,3 ± 2,9 seconds vs 13,4 ± 1,7 seconds; tear meniscus height, 290,3 ± 133,6 μm vs 459,8 ± 180,3 μm, respectively). In addition, the OSDI score in the antidepressants group was significantly higher than in the control group (31,1 ± 21,2 ve 17,4 ± 11,8, respectively).…”
Section: Discussionmentioning
confidence: 86%